True three-dimensional cone-beam reconstruction (TTCR) algorithm - Lee, S.Z.; Ra, J.B.; Hilal, S.K.; Cho, Z.H. (IEEE transactions on medical imaging, 1989)
A true three-dimensional cone-beam reconstruction (TTCR) algorithm for direct volume image reconstruction from 2-D cone-beam projections is developed for the complete sphere geometry. The algorithm is derived from the parallel-beam true three-dimensional reconstruction (TTR) algorithm and is based on the modified filtered backprojection technique, which uses a set of 2-D space-invariant filters. The proposed algorithm proved to be superior in spatial resolution to the parallel-beam TTR algorithm and to offer better computational efficiency.< >